Comparison of the Impact of Traditional Games and Small Games on Students' Physical Fitness - Yovira, May Nadira; HB, Bafirman; Barlian, Eri; Emral, Emral; Zarya, Fiky (Department of Physical Education, Sport, Health and Recreation, 2023)
The purpose of this study is for teachers to know which game method is more feasible to use for the preparation of physical education learning programs on physical fitness. This type of research is quantitative associative with a quasi-experimental approach. The design of this study is a 2 x 2 factorial design. The population in this study was all students of SDN 67/V Tanjung Bojo, Batang Asam District, Tanjung Jabung Barat Regency, Jambi, totaling 117 people. Samples were taken using probability sampling, namely proportionate stratified random sampling divided by simple random sampling totaling 24 students, then grouped using matching ordinal pairing. The research instrument uses the TKJI test (Indonesian Physical Fitness Test). Data were analyzed by path analysis through 2-path AVAVA testing at α = 0.05. The results of hypothesis testing show: (1) There are differences in the level of physical fitness based on the provision of game forms where it is found in the table of hypothesis test results on the game row that a significance value of 0.000 is obtained, (2) There are differences in physical fitness levels based on test tests where there is a hypothesis test result table on the test row obtained a significance value of 0.001, (3) There is an interaction between game forms and test tests in determining the level physical fitness where found in the table of hypothesis test results in the test game row obtained a significance value of 0.04, (4) The average value of pre-test results of the physical fitness level of children who were given small games (15,917) was higher than children who were given traditional games (13,833), (5) The average post-test score of the physical fitness level of children given small games (15.33) was higher than children who were given traditional games (17,500). It was concluded that the provision of learning programs with small or traditional game methods both have an influence on students' physical fitness, but small games with modifications focused on students will have more influence on physical fitness